A comparative analysis of the efficiency of international education systems Applying Data Envelopment Analysis (DEA) - BEN HEMZA Asmaa; ESSARDI Moulay Omar (African Scientific Journal, 2024)
Abstract The purpose of this study is to identify and examine the efficiency of the education system from a cross-national perspective. We used Data Envelopment Analysis to examine data from 43 countries from various world regions and income groups. The goal of this study is to fill a gap in the existing literature by focusing on other outcomes of the education system rather than the standardized test scores of students, which have been mainly used by the authors. The results reveal that disparities exist between countries in the same region and socioeconomic category. Thus, regardless of the country's economic level, the country's education system can be improved. Our findings also provide us with a detailed analysis of the input and output slacks, with the goal of highlighting areas where a country can improve its performance by increasing output levels without requiring additional inputs on the one hand, or providing insights into opportunities for improvement and resource allocation to increase outputs without requiring additional resources, simply by using its existing inputs more efficiently or fully on the other hand. Keywords Technical efficiency, Education system, DEA, Cross-country Analysis.